Study on Blood Biochemical Profile in Relation to Age and Scrotal Biometry in Adolescent Surti Bucks - Chaudhri, DV; Dhami, AJ; Parmar, CP; Patel, JA (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was undertaken on 11 Surti male kids of identical age and birth weight from 14 weeks of age till puberty and sexual maturity up to 47 weeks (12 months) of age. The scrotal biometry, i.e., length, width, circumference (cm) and volume (cm3) were recorded using standard procedures at 3 weeks intervals. The mean weight of animals at birth, 14 and 35 weeks of age was 1.53±0.05, 9.86±0.61 kg and 17.84±1.09 kg, respectively and thereafter it did not change much till 47 weeks of age. Similarly, the mean values of scrotal length, width, circumference (cm) and scrotal volume (cm3) at 14 weeks of age were 2.89±0.22, 2.05±0.17, 8.82±0.72 and 21.36±0.93, respectively, which then gradually increased with an advancing age till 35 weeks of age reaching 10.65±0.30, 7.55±0.24, 19.45±0.65 and 200.45±16.67, respectively, which later became almost stable. At puberty, the average age and body weight were 27.00±0.75 weeks and 15.16±0.56 kg, and at sexual maturity 38.18±0.90 weeks and 19.61±0.93 kg, respectively. Great individual variation was noted in all the biometric traits among bucks studied. The blood plasma profile studied at bimonthly intervals revealed significant increase in total protein and ALT, and decrease in cholesterol and cobalt concentrations with advancing age. However, the AST and macro-micro minerals did not vary, suggestive of acquiring adult profile by 6 months of age. Based on the age, scrotal biometry, semen quality and blood biochemistry, it could be inferred that the Surti bucks attained full reproductive potential at around 9- 10 months of age with stable blood plasma profile.
Keywords: Surti buck; Adolescence; Scrotal biometry; Blood; Maturity